2017
DOI: 10.1536/ihj.16-359
|View full text |Cite
|
Sign up to set email alerts
|

Is Serum Uric Acid Independently Associated With Left Ventricular Mass Index, Ejection Fraction, and B-Type Natriuretic Peptide Among Female and Male Cardiac Patients?

Abstract: SummaryMean serum uric acid (SUA) levels are higher in men than women. In addition, recent studies have suggested that the SUA threshold at which the cardiovascular risk might increase may vary between women and men. In the current retrospective study, by analyzing the data from 219 female and 519 male patients who were free from uric acid-lowering medication, we investigated whether SUA is associated with left ventricular mass index (LVMI), left ventricular ejection fraction (LVEF), and plasma levels of B-typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 42 publications
1
8
0
1
Order By: Relevance
“…Elevated SUA has been considered to be correlated to cardiovascular diseases, including hypertension, 20) stroke, 21) chronic heart failure, 22,23) myocardial infarction, 24) atrial fibrillation, 25) and left ventricular hypertrophy. 26) The present results were in agreement with the finding reported by Yamada, et al, 27) which revealed that the SUA level is an independent predictor of ventricular arrhythmia in patients with left ventricular hypertrophy. In addition, in the present study, gender-specific analyses were performed, and a significant correlation between elevated SUA levels and PVC prevalence in males, but not in females, was found.…”
Section: Discussionsupporting
confidence: 94%
“…Elevated SUA has been considered to be correlated to cardiovascular diseases, including hypertension, 20) stroke, 21) chronic heart failure, 22,23) myocardial infarction, 24) atrial fibrillation, 25) and left ventricular hypertrophy. 26) The present results were in agreement with the finding reported by Yamada, et al, 27) which revealed that the SUA level is an independent predictor of ventricular arrhythmia in patients with left ventricular hypertrophy. In addition, in the present study, gender-specific analyses were performed, and a significant correlation between elevated SUA levels and PVC prevalence in males, but not in females, was found.…”
Section: Discussionsupporting
confidence: 94%
“…Fujita et al reported that SUA levels were independently associated with LVH with an OR of 2.79 in 116 male patients with cardiac diseases [ 9 ]. Yamauchi et al showed that SUA levels were associated with LVH, independent of confounding factors, including fibroblast growth factor (FGF) 23 and diuretics in 219 and 519 female and male patients with cardiac diseases, respectively, who were free from uric acid-lowering medications [ 19 ]. Concerning LVDD, Cicoira et al reported that increased SUA levels were associated with LVDD in 150 patients with dilated cardiomyopathy [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…ric acid is synthesized by the liver during purine metabolism, and serum uric acid levels are determined by the balance between uric acid production and excretion. It has been reported that the uric acid level is associated with incident cardiovascular disease (CVD) and its risk factors, [1][2][3][4][5] which include high blood pressure, diabetes, dyslipidemia, smoking, and obesity. Although these risk factors alone can cause CVD, it has been suggested that the risk of CVD development increases if factors overlap, even if each factor is low.…”
mentioning
confidence: 99%